Implementation of Decision Support System in Choosing the Best E-Wallet using ROC and MOORA Weighting Methods - Mesran, Mesran; Qomaini, Ahmad; Sirait, Ika Paulina; Rosnizam, Rosnizam (Bulletin of Informatics and Data Science, 2024)
This research aims to analyze digital wallet usage preferences among university students using a decision support system. With the rise of various digital wallet services such as DANA, LinkAja, and GoPay, students often have difficulty in choosing the platform that best suits their needs. To solve this problem, the research uses a combination of the Rank Order Centroid (ROC) and Multi-Objective Optimization by Ratio Analysis (MOORA) methods. The ROC method was used to determine the criteria weights, while MOORA was applied to rank the digital wallet alternatives. The criteria used in this study include merchant range, cashback program, transaction fees, and ease of use. The research sample consisted of 150 students from the Faculty of Economics, Universitas Nusantara. The results showed that GoPay ranked first as the most preferred digital wallet, followed by DANA in second place, and LinkAja in third. The findings are expected to help students in choosing the digital wallet that best suits their preferences, as well as provide input for digital wallet service providers to improve their service quality